Why Critical Thinking Can and Often Does Fail Us in Solving Serious Real-World Problems: A Three-Track Model of Critical Thinking - Robert J. Sternberg; Aurora Jo Hayes (Journal of Intelligence, 2025)
This article deals with how love and hatred of ideas can influence, and often distort or suppress, critical thinking. Love and hate can serve adaptive intellectual functions, but in practice, they often manifest in maladaptive ways. The article reviews the role of critical thinking in adaptation, then discusses how love and hate can influence critical thinking. The article suggests that teaching critical thinking needs to take into account that real-world critical thinking often bears little resemblance to that shown in tests or in school. We need to teach critical thinking as it exists in the world, not in rarefied settings.